2015
DOI: 10.7763/joebm.2015.v3.294
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethical Leadership on Employee‟s Virtuous Behavior – A Study of Marketing Agencies in Ho Chi Minh City, Vietnam

Abstract: This study examined the effect of ethics-based leadership on employee virtuous-ethical behavior with an aim to improve the ethical behaviors among employees in the marketing agencies in Ho Chi Minh City. Qualitative method was applied and questionnaire survey was directly delivered to 283 respondents. This study argued that in order to increase employee virtuous-ethical behavior, marketing agencies should do the followings a) conduct the ethical course in their educational program, b) emphasize the people have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Brown et al [11] reported that little research has been done on the ethical dimension of leadership. While several styles of leadership have emerged (e.g., transformational and authentic leadership), most of the recent attention had been paid to ethical leadership as part of these styles, not as an independent style [9,10,[12][13][14]16]. Brown et al [11] constructed an instrument to assess ethical leadership and examine its predictive validity for significant staff results.…”
Section: The Relationship Between Ethical Leadership and Intention Tomentioning
confidence: 99%
See 4 more Smart Citations
“…Brown et al [11] reported that little research has been done on the ethical dimension of leadership. While several styles of leadership have emerged (e.g., transformational and authentic leadership), most of the recent attention had been paid to ethical leadership as part of these styles, not as an independent style [9,10,[12][13][14]16]. Brown et al [11] constructed an instrument to assess ethical leadership and examine its predictive validity for significant staff results.…”
Section: The Relationship Between Ethical Leadership and Intention Tomentioning
confidence: 99%
“…Many previous researchers empirically showed that employee positive ethical behavior was directly affected by factors of ethical leadership [9,[12][13][14]. This study attempted to further explore the possible relationship between ethical leadership and psychological capital.…”
Section: The Relationship Between Ethical Leadership and Psychologicamentioning
confidence: 99%
See 3 more Smart Citations